LANGUAGE AND CULTURE LEARNING STRATEGIES IN A STUDY ABROAD CONTEXT - Róg, Tomasz (Neofilolog, 2018)
This article takes a step towards bridging the research gap between language-and-culture learning strategies and SLA-oriented outcomes of study abroad programmes. While studies concerning the impact of studying in foreign countries document various language-related benefits of the experience, only a handful addresses the types of language and culture learning strategies employed by study abroad participants. The present study tracks the use of these strategies by Polish students of English philology participating in a semester-long exchange programme in Portugal and Romania. It is revealed that although the use of language and culture learning strategies does not change significantly over the course of students’ stay abroad, the strategies chosen before their departure are used rather consistently.